Disciplina e indisciplina na aula: uma perspectiva sociológica - Luciano Campos da Silva (2007)
The analysis of the literature on school indiscipline points to a trend, on the part of the investigators, to establish a direct relationship between an increase in this phenomenon in the classroom and the growing access of the lower socioeconomic classes to schools. This view, which is weakly supported by empirical evidence, is also frequently detected in statements made by teachers and students, which ends up contributing to a kind of disqualification of the students and families from these socioeconomic sectors. In the belief, however, that students and families from the lower socioeconomic rungs do not constitute a homogenous reality, this research sought to investigate, from a sociological perspective, the constitution of in/discipline in two classrooms at a municipal elementary school in Belo Horizonte, located in a district on the outskirts of the capital. The general purpose was to identify some internal and external conditions at the school that could explain the different behaviors of students from the lower socioeconomic class in view of school discipline. The collection of data was done mainly through direct observation, over a period of one year, of the two classrooms that were investigated and by conducting semi-structured interviews of students, teachers, and parents. The analysis of the data indicates the possibility of a conceptual distinction between indiscipline and violence and corroborates other investigations that have emphasized the not very serious nature and merely perturbing of the conditions of production in the class of the greater part of the deviant behavior occurring in the classroom. However, it should be pointed out that, although not very serious, behavioral incidents of indiscipline take on, in specific circumstances, highly disturbing forms from a pedagogical viewpoint. The results further indicate the existence of a variation in the frequency with which students participate in episodes of indiscipline, with three general types of students having been identified: frequently disciplined, frequently undisciplined and occasionally undisciplined. Each one of these types is affected in a singular manner by changes that occur in the school context in relation to disciplinary and pedagogical characteristics and by the relationship with their teachers. An analysis of the family life of some case-students and the characteristics of the teaching staff indicates that incidents of indiscipline in the classroom find their conditions of possibility in an admixture of family and school factors